(15)N(2) Fixation by Bacteria Associated with Maize Roots at a Low Partial O(2) Pressure - Alexander, David B. (1989)
Nitrogen fixation by bacteria associated with roots of intact maize plants was measured by exposing the roots to (15)N(2) at a partial O(2) pressure (pO(2)) of 2 or 10 kPa. The plants were grown in a mixture of Weswood soil and sand and then transferred to plastic cylinders containing an N-free plant nutrient solution. The solution was sparged continuously with a mixture of air and N(2) at a pO(2) of 2 or 10 kPa. Acetylene reduction was measured after the roots were exposed to the low pO(2) overnight. The air-N(2) atmosphere in the cylinders was then replaced with an O(2)-He atmosphere at the same pO(2), and the roots were exposed to 20 kPa of (15)N(2) for 20 to 22 h. Incorporation of (15)N into the roots was 200 times greater at 2 kPa of O(2) than at 10 kPa of O(2). Adding l-malate (1 g of C liter(−1)) to the nutrient solution increased root-associated nitrogenase activity, producing a strong (15)N label which could be traced into the shoots. Fixed (15)N was detected in the shoots within 5 days after the plants were returned to unfertilized soil. In a similar experiment with undisturbed plants grown in fritted clay, movement of fixed (15)N into the shoots was evident within 4 days after the roots were exposed to (15)N(2) at 2 kPa of O(2). Inoculation with Azospirillum lipoferum yielded no significant differences in shoot dry weight, total nitrogen content, percent nitrogen, or (15)N enrichment of plant tissues. Inoculated plants did exhibit greater root dry weight than uninoculated plants, however.